Recém nascido de baixo risco: perfil de saúde e boas práticas em uma maternidade de referência - ALBUQUERQUE, Juliana Santos de (2020)
INTRODUCTION: Faced with initiatives in other countries, Brazil following the guidelines of the World Health Organization (WHO), implemented in 2000 the Prenatal and Birth Humanization Program (PHPN) and published in 2001 the Manual of Childbirth, Abortion and Puerperium: humanized care for women, both initiatives aimed at promoting a humanized, qualified and integrated care in prenatal, childbirth and postpartum and throughout the puerperal pregnancy cycle. Being the precursor of practices related to immediate care of the newborn. Such practices, defined by the World Health Organization as good practices for the newborn, include late umbilical cord clamping, immediate motherinfant skin-to-skin contact, early initiation of breastfeeding, kangaroo method, among others. Such practices related to childbirth and newborn care vary among institutions and under socioeconomic and cultural aspects, affecting the quality of care offered. OBJECTIVE: To describe the maternal and neonatal profile of healthy newborns and to identify the good practices adopted in a maternal and child reference institution in the city of Belém - Pará. METHOD: This is an exploratory, documentary and descriptive study of cross-sectional design. quantitative nature, developed at the Santa Casa de Misericórdia do Pará Foundation, in the Joint Accommodation. A sample of 100 postpartum women and 100 hospitalized newborns were obtained. The collection took place from July to November 2019, after approval by the Research Ethics Committee. Information was obtained through interviews and analysis of hospital records. RESULTS: Predominated in the sample of postpartum women from the metropolitan region, with an average of 7 prenatal consultations, fixed partners in more than half of the sample, highlighting the public service in neonatal follow-up, in compliance with the established by the Ministry of Health. newborn weight greater than or equal to 2,500kg, gestational age of 38 weeks giving pregnancy at term, APGAR at 1 minute greater than 7 and at 5 minutes ≥ 9, head circumference 34 cm, defining adequate and healthy conditions of birth. Good practices regarding breastfeeding, skin-to-skin contact meet satisfactory parameters stipulated by the World Health Organization. CONCLUSION: The research sought to address the issues related to low-risk maternal and child care. New studies aimed at this public are important to define the behaviors taken in face of this profile. Conveying to this binomial the right to health in the face of human fullness.